How my clinical placement in Australia helped me to become the clinician I am today - Lynham, S.; Cocks, Naomi; Philips, E.; Mulae, A.; Fletcher, H.; Smith, L. (Speech Pathology Australia, 2013)
In the global society in which we live the graduate speech-language pathologist needs to be prepared for working with a culturally diverse client group and for the possibility that they may work in a country other than the one in which they trained. International clinical placement opportunities are a common method for many Australian speech language pathology programs to prepare students for an international career and for working with a culturally diverse client group. There have been many reported benefits for students taking part in these placements. But what are the benefits for overseas students who participate in a placement in Australia? This clinical insights article asked five clinicians who had trained in the UK and who had completed a placement in Australia during their training to reflect on this experience. They reported many benefits both personally and professionally. They felt that their Australian placement experience prepared them to work with a culturally diverse client group and shaped who they areas clinicians. There were also additional benefits for the service in which they now worked.